Analyzing the Islamic Securities Crowdfunding System through the Lens of Maqashid Sharia - Mesi Herawati (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
This study aims to examine the aspects of maqashid sharia in the context of the Islamic securities crowdfunding system. Employing qualitative research methods through library studies, the findings reveal that among the six management aspects in Islamic securities crowdfunding, five elements of maqashid sharia are addressed: protection of religion (hifz ad-din), protection of life (hifz an-nafs), protection of intellect (hifz al-aql), protection of lineage (hifz an-nasl), and protection of property (hifz al-mal). Nonetheless, the aspect of risk management necessitates further enhancement, as effective risk management is essential for safeguarding the interests of both investors and MSMEs regarding asset protection (hifz al-mal). By prioritizing the risk management dimension, the framework can not only uphold the maqashid sharia related to asset protection but also contribute to the overall sustainability of the Islamic securities crowdfunding financial system